High speed storage area networks using a fibre channel arbitrated loop interconnect. - Heath, J.R (IEEE Network : the magazine of global information exchange)
Fibre channel arbitrated loops offer a new approach to realizing high-speed storage interconnection networks. We describe an FC-AL topology and FC-AL protocols for storage networks. In particular, we describe channel arbitration, signaling and transmission protocols, and the fibre channel mapping protocol for SCSI. A simulation model of FC-AL storage networks is described. Performance results derived from the model are presented and are used to investigate the FC-AL storage network performance